Preparation method of wireless charging coil and wireless charger
Through a new wireless charging coil preparation method, the gap between the electrode and the magnetic chip is eliminated through integrated sintering, the problems of large power loss and pollution in the traditional method are solved, and efficient and environmentally friendly wireless charging coil preparation is achieved.
Patent Information
- Application Number
- CN202411831675.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The preparation method of traditional wireless charging coils has problems such as low production efficiency, high manufacturing cost, large power loss and pollution.
A new preparation method is adopted, including preparing a dielectric magnetic powder slurry, preparing a ferrite dielectric diaphragm, preparing a bar block slurry, providing electrode slurry, preparing insulated ferrite slurry, screen printing, lamination treatment, glue discharge and sintering treatment and preparing wireless charging coils. Through these steps, the magnetic sheet, electrode and insulating magnetic material are integrated sintered to eliminate the gap between the electrode and the magnetic sheet and improve the power conversion efficiency.
It achieves gap-free loss, improves power conversion efficiency, current resistance characteristics and transmit power, and reduces manufacturing costs and pollution problems, and has the characteristics of energy-saving and environmentally friendly.
Smart Images

Figure CN119650291A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of wireless charging, and in particular relates to a method for preparing a wireless charging coil and a wireless charger. Background Art
[0002] With the rapid development of electronic information technology, electronic products have occupied an irreplaceable and important position in people's lives. Wireless charging technology, with its convenience, compatibility and non-contact nature, can reduce plug-in and unplug problems, and can also avoid problems such as poor contact and inappropriate interfaces. In addition, multiple receiving devices can be charged on the same wireless charging device, which solves the problem of wireless charging devices being restricted by lines and realizes the complete separation of power supply and electrical appliances. Compared with traditional chargers, it has the advantages of flexibility and safety.
[0003] However, the traditional method for preparing wireless charging coils has the following disadvantages: 1. Low production efficiency and the coil needs to be prepared separately; 2. High manufacturing cost and the grinding of magnetic sheets produces polluted water; 3. The motor coil is attached to the magnetic sheet, resulting in a gap between the electrode coil and the magnetic sheet, thereby increasing power loss and reducing power conversion efficiency.
[0004] Therefore, the present invention provides a method for preparing a wireless charging coil and a wireless charger to solve the above technical problems. Summary of the invention
[0005] In view of the above problems, the object of the present invention is to provide a method for preparing a wireless charging coil and a wireless charger, which have no gap power loss, high power conversion efficiency, and are energy-saving and environmentally friendly.
[0006] The present invention provides a method for preparing a wireless charging coil, comprising the following steps:
[0007] S1, preparing a medium magnetic powder slurry: providing a grinding ball unit, a first ferrite magnetic powder and a first solvent, and mixing the grinding ball unit, the first ferrite magnetic powder and the first solvent according to a preset ratio to form a first mixture; adding an appropriate amount of a plasticizer, a dispersant and a defoaming agent to the first mixture to form a second mixture; ball milling or sand milling the second mixture, and adding a binder resin to the second mixture after ball milling or sand milling to form a third mixture; ball milling or sand milling the third mixture to form a first slurry, and performing a first pretreatment on the first slurry to form a medium magnetic powder slurry;
[0008] S2, preparing a ferrite dielectric diaphragm: placing the dielectric magnetic powder slurry in a tape casting machine for tape casting to form first dielectric diaphragms of different thicknesses, and cutting the first dielectric diaphragms according to a preset size to form ferrite dielectric diaphragms;
[0009] S3, preparing a block diaphragm: laminating the ferrite dielectric diaphragm to form a block diaphragm;
[0010] S4, providing electrode slurry, wherein the electrode slurry is a metal conductive slurry;
[0011] S5, preparing insulating ferrite slurry: providing a second ferrite magnetic powder, and adding an appropriate amount of a second solvent, a binder, a plasticizer and a dispersant to the second ferrite magnetic powder to form a second slurry, and stirring the second slurry at a high speed; placing the second slurry after high-speed stirring on the rolling mill for rolling treatment, and performing a second pretreatment on the second slurry after rolling treatment to form an insulating ferrite slurry; wherein the amount of the binder added is 15%-90% of the content of the second ferrite magnetic powder;
[0012] S6, screen printing process: fix the block diaphragm at a preset position of the screen printer stage, and print 1-2 layers of electrode slurry with a preset thickness on the block diaphragm according to a preset pattern, and then dry it to form an electrode magnetic sheet; print 1-2 layers of insulating ferrite slurry with a preset thickness on the electrode magnetic sheet, and then dry it to form a first magnetic sheet coil;
[0013] S7, lamination treatment: vacuum-packing the first magnetic sheet coil, performing water pressure treatment on the vacuum-packed first magnetic sheet coil, and cutting or punching the water pressure treated first magnetic sheet coil to form a second magnetic sheet coil;
[0014] S8, debinding and sintering treatment: performing debinding and sintering treatments on the second magnetic sheet coil in sequence to form a third magnetic sheet coil;
[0015] S9, preparing a wireless charging coil: cleaning, welding leads, testing and packaging the third magnetic sheet coil in sequence to form a wireless charging coil.
[0016] Preferably, the first ferrite magnetic powder is a high resistivity soft magnetic material greater than 1KΩ / mm, and the particle size range of the soft magnetic material is 0.1μm-5μm; the ratio of mixing the grinding ball unit, the first ferrite magnetic powder and the first solvent in S1 is: (2-5): (0.5-2): (0.5-2); the grinding ball unit includes two or more grinding balls of different diameters mixed in a ratio of 1:1, and the contour shape of the grinding balls can be circular or cylindrical; wherein the first solvent is formed by mixing ester solvents, alcohol solvents and benzene solvents in pairs, and the mixing ratio of any two solvents among the ester solvents, the alcohol solvents and the benzene solvents is (3-9): (7-1); wherein the ester solvents include n-propyl acetate and ethyl acetate; the alcohol solvents include ethanol, isobutyl alcohol and isopropyl alcohol; the benzene solvents include toluene; the binder resin is polyvinyl butyral or acrylic resin, and the degree of polymerization molecular weight of the polyvinyl butyral is less than or equal to 100,000. The amount of the plasticizer added in S1 is 0.5%-3% of the content of the first ferrite magnetic powder, the amount of the dispersant added is 0.2%-3% of the content of the first ferrite magnetic powder, and the amount of the defoaming agent added is 0.2%-3% of the content of the first ferrite magnetic powder, wherein the plasticizer includes dioctyl phthalate, dibutyl phthalate and polymerized ester.
[0017] Preferably, in S1, the second mixture and the third mixture are ball-milled by a ball mill, and the rotation speed of the ball mill is 20 rpm-80 rpm, the second mixture is ball-milled for 4h-15h, and the third mixture is ball-milled for 5h-30h.
[0018] Preferably, in S1, the second mixture and the third mixture are sand ground by a sand mill, and the time for sand grinding the second mixture is 20min-120min, and the second mixture needs to be stirred before sand grinding, and the stirring time is 10min-30min; the time for sand grinding the third mixture is 40min-300min.
[0019] Preferably, the tape casting machine is any one of a rigid tape casting machine, a carrier tape casting machine and a wet tape casting machine; the first pretreatment includes a first index detection and a first vacuum treatment, the first index includes the viscosity, solid content and density of the first slurry; the second pretreatment includes a second index detection and a second vacuum treatment, the second index includes the viscosity, solid content and fineness of the second slurry; the metal conductive paste is any one of a gold conductive paste, a silver conductive paste and a copper conductive paste, and the solid content of the metal conductive paste is 85%-95%, the metal particle size in the metal conductive paste ranges from 0.5μm to 3.0μm, and the thixotropic coefficient of the metal conductive paste is 5-50.
[0020] Preferably, in S3, the ferrite dielectric diaphragm is stacked to form a bar block diaphragm, specifically including: S31, stacking the bar block diaphragms neatly according to preset requirements; S32, pre-pressing the neatly stacked bar block diaphragms, the pre-pressing pressure value is 0.1 tons-10 tons, and the pre-pressing time is 0.5min-10min.
[0021] Preferably, the preparation method of the adhesive in S5 specifically includes: providing a resin and a third solvent; mixing the resin and the third solvent, stirring and dissolving them at a temperature of 30°C-80°C to form the adhesive; wherein the resin includes polyvinyl butyral, cellulose resin and acrylic resin, and the ratio of the polyvinyl butyral, the cellulose resin and the acrylic resin is: (5-10): (3-5): (1-2), and at least one of the polyvinyl butyral, the cellulose resin and the acrylic resin has a molecular weight of polymerization greater than or equal to 1000; the solvent accounts for 50%-85% of the adhesive, and the solvent is an alcohol solvent or an ester solvent.
[0022] Preferably, the screen printer stage fixes the block diaphragm by means of a vacuum suction cup; in S6, the electrode slurry and the insulating ferrite slurry are printed by scraping glue, and the hardness of the scraper material is 50 degrees-95 degrees, and the scraper angle is 25 degrees-80 degrees; in S7, the first magnetic sheet coil after vacuum packaging is subjected to water pressure treatment, specifically including: placing the first magnetic sheet coil after vacuum packaging in water with a water temperature of 10°C-90°C, and subjecting the first magnetic sheet coil to water pressure treatment, the water pressure treatment time is 5min-100min, and the pressure value of the water pressure treatment is 0.05 tons / square centimeter-1 ton / square centimeter.
[0023] Preferably, the binder removal curve of the binder removal treatment is heating, insulation and cooling, and the heating rate in the binder removal treatment is 2°C / min-8°C / min, the maximum temperature of the binder removal treatment is 500°C, and the time of the binder removal treatment is 2h-6h; the sintering treatment adopts air sintering, and the sintering curve of the air sintering is heating, insulation and cooling, the heating time of the air sintering is 20h-50h, the insulation temperature of the air sintering is 880°C-930°C, and the cooling time of the air sintering is 5h-20h; wherein, dried air is added during the heating and cooling process of the air sintering.
[0024] The present invention also provides a wireless charger, which comprises a wireless charging coil prepared by the above method.
[0025] Compared with the related art, the present invention provides a method for preparing a wireless charging coil, and its preparation process includes: preparing dielectric magnetic powder slurry, preparing ferrite dielectric diaphragm, preparing block diaphragm, providing electrode slurry, preparing insulating ferrite slurry, screen printing, lamination, debinding sintering and preparing wireless charging coil. Through the above process flow, the magnetic sheet, electrode and insulating magnetic material are sintered in an integrated manner, so that the electrode and the magnetic sheet can be closely connected without gap loss, which not only improves the power conversion efficiency, current resistance and transmission power, but also improves product performance and heat dissipation effect; at the same time, the wireless charging coil manufactured by the above preparation method will not produce wastewater and other pollution problems during the production process, and has the characteristics of energy saving and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of a process of preparing a wireless charging coil of the present invention;
[0027] Figure 2 It is a schematic diagram of the process of laminating ferrite dielectric diaphragms to form a block diaphragm in the present invention;
[0028] Figure 3 It is the printed pattern of the electrode paste printed on the block membrane in the present invention. DETAILED DESCRIPTION
[0029] The present invention provides a method for preparing a wireless charging coil, aiming to solve the problems of large power loss, low power conversion efficiency, high manufacturing cost and pollution in a traditional method for preparing a wireless charging coil.
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Please see attached Figure 1-3 As shown, the present invention provides a method for preparing a wireless charging coil, comprising the following steps:
[0032] S1, preparing medium magnetic powder slurry: providing a grinding ball unit, a first ferrite magnetic powder and a first solvent, and mixing the grinding ball unit, the first ferrite magnetic powder and the first solvent according to a preset ratio to form a first mixture; adding an appropriate amount of plasticizer, dispersant and defoaming agent to the first mixture to form a second mixture; ball milling or sand milling the second mixture, and adding a binder resin to the second mixture after ball milling or sand milling to form a third mixture; ball milling or sand milling the third mixture to form a first slurry, and performing a first pretreatment on the first slurry to form a medium magnetic powder slurry.
[0033] Specifically, the first ferrite powder is a soft magnetic material with a high resistivity greater than 1KΩ / mm, and the particle size range of the soft magnetic material is 0.1μm-5μm (measured by a particle size analyzer or a SEM electron microscope); the first pretreatment includes a first indicator detection and a first vacuum treatment, and the first indicator includes the viscosity, solid content and density of the first slurry.
[0034] In this embodiment, the mixing ratio of the grinding ball unit, the first ferrite magnetic powder and the first solvent is: (2-5): (0.5-2): (0.5-2); the grinding ball unit includes two or more grinding balls of different diameters mixed in a ratio of 1:1, and the contour shape of the grinding balls can be circular or cylindrical; wherein the first solvent is formed by mixing ester solvents, alcohol solvents and benzene solvents in pairs, and the mixing ratio of any two solvents among the ester solvents, the alcohol solvents and the benzene solvents is (3-9): (7-1); wherein the ester solvent can be n-propyl acetate, ethyl acetate or other lipid series; the alcohol solvent can be ethanol, isobutyl alcohol, isopropyl alcohol and other alcohols; the benzene solvent includes toluene or other benzene series; the binder resin is polyvinyl butyral or acrylic resin, and when it is polyvinyl butyral, the molecular weight of the polymerization degree of polyvinyl butyral is less than or equal to 100,000.
[0035] Furthermore, the second mixture and the third mixture are ball-milled by a ball mill, and the rotation speed of the ball mill is 20 rpm-80 rpm, and the time for ball-milling the second mixture is 4h-15h; the time for ball-milling the third mixture is 5h-30h. Of course, the second mixture and the third mixture can also be sand-milled by a sand mill. When sand-milling, the time for sand-milling the second mixture is 20min-120min, and the second mixture needs to be stirred before sand-milling, and the stirring time is 10min-30min, and the time for sand-milling the third mixture is 40min-300min.
[0036] In this embodiment, the amount of the plasticizer added in S1 is 0.5%-3% of the content of the first ferrite magnetic powder, the amount of the dispersant added is 0.2%-3% of the content of the first ferrite magnetic powder, and the amount of the defoaming agent added is 0.2%-3% of the content of the first ferrite magnetic powder, wherein the plasticizer includes dioctyl phthalate, dibutyl phthalate and polymer ester.
[0037] S2, preparing a ferrite dielectric diaphragm: placing the dielectric magnetic powder slurry in a tape casting machine for tape casting to form first dielectric diaphragms of different thicknesses, and cutting the first dielectric diaphragms according to a preset size to form ferrite dielectric diaphragms.
[0038] In this embodiment, the tape casting machine is any one of a steel tape casting machine, a carrier tape casting machine and a wet tape casting machine; and the first dielectric membrane is cut to form a ferrite dielectric membrane of a certain size, and its size can be adjusted according to actual conditions.
[0039] S3, preparing a block diaphragm: laminating the ferrite dielectric diaphragm to form a block diaphragm.
[0040] In this embodiment, the ferrite dielectric diaphragm is stacked to form a bar block diaphragm, specifically including: S31, stacking the bar block diaphragms neatly according to preset requirements; S32, pre-pressing the neatly stacked bar block diaphragms, the pre-pressing pressure value is 0.1 tons-10 tons, and the pre-pressing time is 0.5min-10min; of course, the pre-pressing pressure value and pre-pressing time are set according to the required thickness of the bar block diaphragm.
[0041] S4, providing electrode slurry, wherein the electrode slurry is a metal conductive slurry.
[0042] In this embodiment, the metal conductive paste is any one of gold conductive paste, silver conductive paste and copper conductive paste, and the solid content of the metal conductive paste is 85%-95%, the metal particle size in the metal conductive paste ranges from 0.5μm to 3.0μm, and the thixotropic coefficient of the metal conductive paste (viscosity at 10 rpm to viscosity at 100 rpm) is 5-50.
[0043] S5, preparing insulating ferrite slurry: providing a second ferrite magnetic powder, and adding an appropriate amount of a second solvent, an adhesive, a plasticizer and a dispersant to the second ferrite magnetic powder to form a second slurry, and stirring the second slurry at a high speed; placing the second slurry after high-speed stirring on the rolling mill for rolling treatment, and performing a second pretreatment on the second slurry after rolling treatment to form an insulating ferrite slurry; wherein the amount of the adhesive added is 15%-90% of the content of the second ferrite magnetic powder.
[0044] It is worth mentioning that the preparation method of the adhesive in S5 specifically includes: providing a resin and a third solvent; mixing the resin and the third solvent and stirring and dissolving them at a temperature of 30°C-80°C to form the adhesive; wherein the resin includes polyvinyl butyral, cellulose resin and acrylic resin, and the ratio of the polyvinyl butyral, the cellulose resin and the acrylic resin is: (5-10): (3-5): (1-2), and at least one of the polyvinyl butyral, the cellulose resin and the acrylic resin has a molecular weight greater than or equal to 1000; the proportion of the solvent in the adhesive is 50%-85%, and the solvent is an alcohol solvent or an ester solvent. The second pretreatment includes a second indicator detection and a second vacuum treatment, and the second indicator includes the viscosity, solid content and fineness of the second slurry.
[0045] S6, screen printing process: fix the block film sheet at a preset position on the screen printing machine stage, and print a preset pattern on the block film sheet (see attached Figure 3 As shown in the figure, 1-2 layers of electrode slurry with a preset thickness are printed and then dried to form an electrode magnetic sheet; 1-2 layers of insulating ferrite slurry with a preset thickness are printed on the electrode magnetic sheet and then dried to form a first magnetic sheet coil.
[0046] In this embodiment, the screen printer stage fixes the block membrane by means of a vacuum suction cup, and then moves to a corresponding position for printing; in S6, the electrode slurry and the insulating ferrite slurry are printed by scraping glue, and the hardness of the scraping glue is between 50 degrees and 95 degrees, and the scraping angle is between 25 degrees and 80 degrees. Figure 3The white part in the figure is the printed electrode paste pattern, which is indicated by the serial number 1 in the figure. Figure 3 The black part in the figure shown is formed by the dielectric magnetic powder slurry and is represented by the serial number 2.
[0047] S7, lamination treatment: vacuum-packing the first magnetic sheet coil, and water-pressing the vacuum-packed first magnetic sheet coil, and cutting or punching the water-pressing treated first magnetic sheet coil to form a second magnetic sheet coil.
[0048] In this embodiment, the first magnetic sheet coil after vacuum packaging is subjected to water pressure treatment in S7, which specifically includes: placing the first magnetic sheet coil after vacuum packaging in water with a water temperature of 10°C-90°C, and subjecting the first magnetic sheet coil to water pressure treatment, the water pressure treatment time is 5min-100min, and the pressure value of the water pressure treatment is 0.05 tons / square centimeter-1 ton / square centimeter. In addition, the first magnetic sheet coil is cut or punched to form a single small piece of the second magnetic sheet coil (including the bottom magnetic isolation sheet and the surface electrode coil), and the time, temperature and pressure value of the water pressure treatment of the first magnetic sheet coil are adjusted and set according to the thickness of the first magnetic sheet coil, and the time, temperature and pressure value of the water pressure treatment are different for different thicknesses.
[0049] S8, debinding and sintering treatment: performing debinding and sintering treatment on the second magnetic sheet coil to form a third magnetic sheet coil.
[0050] In order to ensure the compactness and flatness of the magnetic sheet coil (due to the thinness and large area of the magnetic sheet, it is easy to bend and deform, etc.), in this embodiment, the binder removal curve of the binder removal treatment is heating, insulation and cooling, and the heating rate in the binder removal treatment is 2℃ / min-8℃ / min, the maximum temperature of the binder removal treatment is 500℃, and the time of the binder removal treatment is 2h-6h. In addition, the sintering speed of the sintering treatment after the binder removal treatment should be slow, and the binder removal phenomenon is carried out once in the early stage. Air sintering is used during sintering, and the sintering curve of the air sintering is heating, insulation and cooling. The heating time of the air sintering is 20h-50h, the insulation temperature of the air sintering is 880℃-930℃, and the cooling time of the air sintering is 5h-20h; wherein, the air sintering is added with dried air during the heating and cooling process to ensure that the air is fully oxygenated, improve the insulation resistance value of the magnet sintering, and reduce its own loss.
[0051] S9, preparing a wireless charging coil: cleaning, welding leads, testing and packaging the third magnetic sheet coil in sequence to form a wireless charging coil.
[0052] In this embodiment, the test indicators include size, inductance, Q (quality factor) value, direct current resistance (DCR), wireless charging conversion efficiency and standby power consumption.
[0053] In addition, the present invention also provides a wireless charger, which includes a wireless charging coil prepared by the above method.
[0054] Two specific implementation modes are listed below to further illustrate the present invention;
[0055] Implementation Method 1
[0056] S1, prepare dielectric magnetic powder slurry: select nickel zinc ferrite magnetic powder, whose resistivity is greater than 200MΩ / mm (millimeter), and the particle size of nickel zinc ferrite magnetic powder is 1.8μm. First, mix the grinding ball: nickel zinc ferrite magnetic powder: the first solvent, and the mixing ratio is 2:1:1, and then add plasticizer, dispersant and defoamer. The added amount is calculated according to the proportion of nickel zinc ferrite magnetic powder: plasticizer DOP: 3.5%, dispersant: 0.2%, defoamer: 0.2%. The first solvent used is n-propyl acetate and ethanol in a ratio of 9:1. After the materials are prepared, the adhesive resin is added after ball milling at 45 rpm for 5 hours in a ball mill, and then the viscosity, solid content and density are tested after ball milling for 25 hours. After the test meets the requirements, the dielectric magnetic powder slurry is obtained. The adhesive resin used is polyvinyl butyral (PVB), and the molecular weight of the degree of polymerization of polyvinyl butyral (PVB) is 80,000-90,000.
[0057] S2, preparing a ferrite dielectric diaphragm: casting a first dielectric diaphragm with a thickness of 60 μm on a steel strip casting machine, and cutting the first dielectric diaphragm to obtain a ferrite dielectric diaphragm; and the size of the ferrite dielectric diaphragm is 220 mm×220 mm×0.06 mm.
[0058] S3, preparing a block diaphragm: stacking the cut ferrite dielectric diaphragms neatly according to the design requirements, and then pre-pressing them with a pressure of 0.1 tons for 0.5 minutes to 10 minutes to obtain a block diaphragm.
[0059] S4, providing electrode slurry: the electrode slurry is silver conductive slurry, and the solid content of the silver conductive slurry is 90%.
[0060] S5, prepare insulating ferrite slurry: take ferrite magnetic powder material, add 50% adhesive (accounting for the weight ratio of ferrite magnetic powder material), second solvent, plasticizer, dispersant, etc., stir at high speed, and then roll it on a roller mill twice. After reaching the corresponding required fineness, test the viscosity, solid content, fineness, vacuum, etc., and obtain insulating ferrite slurry after the test meets the preset requirements. The preparation of the adhesive includes: adding resin and the third solvent according to the designed ratio, and stirring and dissolving at 40°C. The resin ratio in the adhesive is: polyvinyl butyral (PVB): cellulose resin: acrylic resin = 6:3:1, and the weight ratio of the solvent in the adhesive is 77.5%.
[0061] S6, screen printing process: fix the block film at the preset position of the screen printer stage, use the vacuum suction cup to suck the film, and then move it to the corresponding position for printing. The hardness of the printing scraper is 75 degrees. Figure 3 As shown in the figure, first print a layer of electrode paste of required thickness and then print a layer of insulating ferrite paste, and dry them after printing to obtain the first magnetic sheet coil.
[0062] S7, lamination treatment: the first magnetic sheet coil after printing and drying is vacuum packed, and then pressed in water at a pressure of 0.2 tons / square centimeter and a temperature of 50°C for 30 minutes, and then cut or punched to obtain the second magnetic sheet coil.
[0063] S8, debinding and sintering treatment: In order to ensure the compactness and flatness of the magnetic sheet coil (due to the thinness and large area of the magnetic sheet, it is easy to bend and deform, etc.), the second magnetic sheet coil is quickly pre-debinded, the debinding heating rate is 2.5℃ / minute, the maximum temperature is 500℃, and the total debinding time is 6 hours; after debinding, sintering is carried out, the sintering speed should be slow, and the debinding should be carried out once in the early stage. Air sintering is used during sintering, and the sintering curve setting should be perfect. The heating time is 50h, the insulation temperature is 890℃, the time is 4h, and the cooling time is 15h. When heating and cooling, it is necessary to set up dried air to ensure that the air is fully oxygenated, improve the insulation resistance value of the magnet sintering, and reduce its own loss. Through this step, the third magnetic sheet coil is obtained.
[0064] S9, preparing a wireless charging coil: cleaning, welding leads, testing and packaging the third magnetic sheet coil in sequence, and obtaining a wireless charging coil after passing the test.
[0065] The test data of the wireless charging coil manufactured by the preparation method of the above embodiment 1 are as follows:
[0066]
[0067] Two specific production methods are listed below to further illustrate the present invention;
[0068] Implementation Method 2
[0069] S1, prepare dielectric magnetic powder slurry: select nickel zinc ferrite magnetic powder, whose resistivity is greater than 100MΩ / mm (millimeter), and the particle size of nickel zinc ferrite magnetic powder is 2μm. First, mix the grinding ball: nickel zinc ferrite magnetic powder: the first solvent, and the mixing ratio is 2:1:1, and then add plasticizer, dispersant and defoamer. The added amount is calculated according to the proportion of nickel zinc ferrite magnetic powder: plasticizer DOP: 3%, dispersant: 0.2%, defoamer: 0.2%. The first solvent used is n-propyl acetate and ethanol in a ratio of 8:2. After the material is prepared, the adhesive resin is added after ball milling at 45 rpm for 5 hours in a ball mill, and then the viscosity, solid content and density are tested for 20 hours. After the test meets the requirements, the dielectric magnetic powder slurry is obtained. The adhesive resin used is polyvinyl butyral (PVB), and the molecular weight of the degree of polymerization of polyvinyl butyral (PVB) is 80,000-90,000.
[0070] S2, preparing a ferrite dielectric diaphragm: casting a first dielectric diaphragm with a thickness of 60 μm on a steel strip casting machine, and cutting the first dielectric diaphragm to obtain a ferrite dielectric diaphragm; and the size of the ferrite dielectric diaphragm is 220 mm×220 mm×0.06 mm.
[0071] S3, preparing a block diaphragm: stacking the cut ferrite dielectric diaphragms neatly according to the design requirements, and then pre-pressing them with a pressure of 0.1 tons for 0.5 minutes to 10 minutes to obtain a block diaphragm.
[0072] S4, providing electrode slurry: the electrode slurry is silver conductive slurry, and the solid content of the silver conductive slurry is 90%.
[0073] S5, prepare insulating ferrite slurry: take ferrite magnetic powder material, add 50% adhesive (accounting for the weight ratio of ferrite magnetic powder material), second solvent, plasticizer, dispersant, etc., stir at high speed, and then roll it on a roller mill twice. After reaching the corresponding required fineness, test the viscosity, solid content, fineness, vacuum, etc., and obtain insulating ferrite slurry after the test meets the preset requirements. The preparation of the adhesive includes: adding resin and the third solvent according to the designed ratio, and stirring and dissolving at 40°C. The resin ratio in the adhesive is: polyvinyl butyral (PVB): cellulose resin: acrylic resin = 6:3:1, and the weight ratio of the solvent in the adhesive is 75%.
[0074] S6, screen printing process: fix the block film at the preset position of the screen printer stage, use the vacuum suction cup to suck the film, and then move it to the corresponding position for printing. The hardness of the printing scraper is 75 degrees. Figure 3As shown in the figure, first print a layer of electrode paste of required thickness and then print a layer of insulating ferrite paste, and dry them after printing to obtain the first magnetic sheet coil.
[0075] S7, lamination treatment: the first magnetic sheet coil after printing and drying is vacuum packed, and then pressed in water at a pressure of 0.2 tons / square centimeter and a temperature of 50°C for 30 minutes, and then cut or punched to obtain the second magnetic sheet coil.
[0076] S8, debinding and sintering treatment: In order to ensure the compactness and flatness of the magnetic sheet coil (due to the thinness and large area of the magnetic sheet, it is easy to bend and deform, etc.), the second magnetic sheet coil is quickly pre-debinded, the debinding heating rate is 4℃ / minute, the maximum temperature is 500℃, and the total debinding time is 4 hours; after debinding, sintering is carried out, the sintering speed should be slow, and the debinding should be carried out once in the early stage. Air sintering is used during sintering, and the sintering curve setting should be perfect. The heating time is 40h, the insulation temperature is 890℃, the time is 4h, and the cooling time is 10h. When heating and cooling, it is necessary to set up dried air to ensure that the air is fully oxygenated, improve the insulation resistance value of the magnet sintering, and reduce its own loss. Through this step, the third magnetic sheet coil is obtained.
[0077] S9, preparing a wireless charging coil: cleaning, welding leads, testing and packaging the third magnetic sheet coil in sequence, and obtaining a wireless charging coil after passing the test.
[0078] The test data of the wireless charging coil manufactured by the preparation method of the above embodiment 2 are as follows:
[0079]
[0080] Compared with the related art, the present invention provides a method for preparing a wireless charging coil, and its preparation process includes: preparing dielectric magnetic powder slurry, preparing ferrite dielectric diaphragm, preparing block diaphragm, providing electrode slurry, preparing insulating ferrite slurry, screen printing, lamination, debinding sintering and preparing wireless charging coil. Through the above process flow, the magnetic sheet, electrode and insulating magnetic material are sintered in an integrated manner, so that the electrode and the magnetic sheet can be closely connected without gap loss, which not only improves the power conversion efficiency, current resistance and transmission power, but also improves product performance and heat dissipation effect; at the same time, the wireless charging coil manufactured by the above preparation method will not produce wastewater and other pollution problems during the production process, and has the characteristics of energy saving and environmental protection.
[0081] The above-described embodiments should be understood as illustrative rather than limiting the scope of protection of the present invention, which is subject to the claims. For those skilled in the art, some non-essential improvements and adjustments made to the present invention still fall within the scope of protection of the present invention without departing from the essence and scope of the present invention.
Claims
1. A method for preparing a wireless charging coil, characterized in that: The preparation method of the wireless charging coil comprises the following steps: S1, preparing a medium magnetic powder slurry: providing a grinding ball unit, a first ferrite magnetic powder and a first solvent, and mixing the grinding ball unit, the first ferrite magnetic powder and the first solvent according to a preset ratio to form a first mixture; adding an appropriate amount of a plasticizer, a dispersant and a defoaming agent to the first mixture to form a second mixture; ball milling or sand milling the second mixture, and adding a binder resin to the second mixture after ball milling or sand milling to form a third mixture; ball milling or sand milling the third mixture to form a first slurry, and performing a first pretreatment on the first slurry to form a medium magnetic powder slurry; S2, preparing a ferrite dielectric diaphragm: placing the dielectric magnetic powder slurry in a tape casting machine for tape casting to form first dielectric diaphragms of different thicknesses, and cutting the first dielectric diaphragms according to a preset size to form ferrite dielectric diaphragms; S3, preparing a block diaphragm: laminating the ferrite dielectric diaphragm to form a block diaphragm; S4, providing electrode slurry, wherein the electrode slurry is a metal conductive slurry; S5, preparing insulating ferrite slurry: providing a second ferrite magnetic powder, and adding an appropriate amount of a second solvent, a binder, a plasticizer and a dispersant to the second ferrite magnetic powder to form a second slurry, and stirring the second slurry at a high speed; placing the second slurry after high-speed stirring on the rolling mill for rolling treatment, and performing a second pretreatment on the second slurry after rolling treatment to form an insulating ferrite slurry; wherein the amount of the binder added is 15%-90% of the content of the second ferrite magnetic powder; S6, screen printing process: fix the block diaphragm at a preset position of the screen printer stage, and print 1-2 layers of electrode slurry with a preset thickness on the block diaphragm according to a preset pattern, and then dry it to form an electrode magnetic sheet; print 1-2 layers of insulating ferrite slurry with a preset thickness on the electrode magnetic sheet, and then dry it to form a first magnetic sheet coil; S7, lamination treatment: vacuum-packing the first magnetic sheet coil, performing water pressure treatment on the vacuum-packed first magnetic sheet coil, and cutting or punching the water pressure treated first magnetic sheet coil to form a second magnetic sheet coil; S8, debinding and sintering treatment: performing debinding and sintering treatments on the second magnetic sheet coil in sequence to form a third magnetic sheet coil; S9, preparing a wireless charging coil: cleaning, welding leads, testing and packaging the third magnetic sheet coil in sequence to form a wireless charging coil.
2. The method for preparing a wireless charging coil according to claim 1, characterized in that: The first ferrite magnetic powder is a high resistivity soft magnetic material greater than 1KΩ / mm, and the particle size of the soft magnetic material ranges from 0.1μm to 5μm; In the S1, the mixing ratio of the grinding ball unit, the first ferrite magnetic powder and the first solvent is: (2-5): (0.5-2): (0.5-2); the grinding ball unit includes two or more grinding balls of different diameters mixed in a ratio of 1:1, and the contour shape of the grinding balls can be circular or cylindrical; wherein the first solvent is formed by mixing an ester solvent, an alcohol solvent and a benzene solvent in pairs, and the mixing ratio of any two solvents among the ester solvent, the alcohol solvent and the benzene solvent is (3-9): (7-1); wherein the ester solvent includes n-propyl acetate and ethyl acetate; the alcohol solvent includes ethanol, isobutyl alcohol and isopropyl alcohol; the benzene solvent includes toluene; the binder resin is polyvinyl butyral or acrylic resin, and the degree of polymerization molecular weight of the polyvinyl butyral is less than or equal to 100,000; The amount of the plasticizer added in S1 is 0.5%-3% of the content of the first ferrite magnetic powder, the amount of the dispersant added is 0.2%-3% of the content of the first ferrite magnetic powder, and the amount of the defoaming agent added is 0.2%-3% of the content of the first ferrite magnetic powder, wherein the plasticizer includes dioctyl phthalate, dibutyl phthalate and polymerized ester.
3. The method for preparing a wireless charging coil according to claim 1, characterized in that: In S1, the second mixture and the third mixture are ball-milled by a ball mill, and the rotation speed of the ball mill is 20 rpm-80 rpm. The second mixture is ball-milled for 4 h-15 h; the third mixture is ball-milled for 5 h-30 h.
4. The method for preparing a wireless charging coil according to claim 1, characterized in that: In S1, the second mixture and the third mixture are sand-milled by a sand mill, and the time for sand-milling the second mixture is 20 minutes to 120 minutes. Before sand-milling the second mixture, the second mixture needs to be stirred, and the stirring time is 10 minutes to 30 minutes; the time for sand-milling the third mixture is 40 minutes to 300 minutes.
5. The method for preparing a wireless charging coil according to claim 1, characterized in that: The tape casting machine is any one of a rigid tape casting machine, a carrier tape casting machine and a wet tape casting machine; the first pretreatment includes a first index detection and a first vacuum treatment, the first index includes the viscosity, solid content and density of the first slurry; the second pretreatment includes a second index detection and a second vacuum treatment, the second index includes the viscosity, solid content and fineness of the second slurry; the metal conductive paste is any one of a gold conductive paste, a silver conductive paste and a copper conductive paste, and the solid content of the metal conductive paste is 85%-95%, the metal particle size in the metal conductive paste ranges from 0.5μm to 3.0μm, and the thixotropic coefficient of the metal conductive paste is 5-50.
6. The method for preparing a wireless charging coil according to claim 1, characterized in that: In the S3, the ferrite dielectric diaphragm is stacked to form a bar block diaphragm, which specifically includes: S31, stacking the bar block diaphragms neatly according to preset requirements; S32, pre-pressing the neatly stacked bar block diaphragms, the pre-pressing pressure value is 0.1 tons-10 tons, and the pre-pressing time is 0.5min-10min.
7. The method for preparing a wireless charging coil according to claim 1, characterized in that: The preparation method of the adhesive described in S5 specifically includes: providing a resin and a third solvent; mixing the resin and the third solvent, stirring and dissolving them at a temperature of 30°C-80°C to form the adhesive; wherein the resin includes polyvinyl butyral, cellulose resin and acrylic resin, and the ratio of the polyvinyl butyral, the cellulose resin and the acrylic resin is: (5-10): (3-5): (1-2), and at least one of the polyvinyl butyral, the cellulose resin and the acrylic resin has a molecular weight of polymerization greater than or equal to 1000; the solvent accounts for 50%-85% of the adhesive, and the solvent is an alcohol solvent or an ester solvent.
8. The method for preparing a wireless charging coil according to claim 1, characterized in that: The screen printer stage fixes the block diaphragm by means of a vacuum suction cup; in S6, the electrode slurry and the insulating ferrite slurry are printed by scraping glue, and the hardness of the scraping glue material is 50 degrees-95 degrees, and the scraping glue angle is 25 degrees-80 degrees; in S7, the first magnetic sheet coil after vacuum packaging is subjected to water pressure treatment, specifically including: placing the first magnetic sheet coil after vacuum packaging in water with a water temperature of 10℃-90℃, and subjecting the first magnetic sheet coil to water pressure treatment, the water pressure treatment time is 5min-100min, and the pressure value of the water pressure treatment is 0.05 tons / square centimeter-1 ton / square centimeter.
9. The method for preparing a wireless charging coil according to claim 1, characterized in that: The debinding curve of the debinding treatment is heating, insulation and cooling, and the heating rate in the debinding treatment is 2°C / min-8°C / min, the maximum temperature of the debinding treatment is 500°C, and the time of the debinding treatment is 2h-6h; the sintering treatment adopts air sintering, and the sintering curve of the air sintering is heating, insulation and cooling, the heating time of the air sintering is 20h-50h, the insulation temperature of the air sintering is 880°C-930°C, and the cooling time of the air sintering is 5h-20h; wherein, dried air is added in the process of heating and cooling of the air sintering.
10. A wireless charger, characterized in that: The wireless charger comprises a wireless charging coil manufactured by the manufacturing method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Production process of wireless-charging magnetic sheet
CN105161279A
Wireless charging device and preparation method thereof
CN106684973A
Low-temperature sintered flexible magnetic sheet and preparation method thereof
CN113716950A
RX Coil for wireless charging using magnetic flexible copper clad laminate(FCCL)
KR1020170037723A